LOFAR detection of a low-power radio halo in the galaxy cluster Abell 990. Issue 1 (18th November 2020) - Hoang, D N; Shimwell, T W; Osinga, E; Bonafede, A; Brüggen, M; Botteon, A; Brunetti, G; Cassano, R; Cuciti, V; Drabent, A; Jones, C; Röttgering, H J A; et al.
ABSTRACT: Radio haloes are extended (∼Mpc), steep spectrum sources found in the central region of dynamically disturbed clusters of galaxies. Only a handful of radio haloes have been reported to reside in galaxy clusters with a mass M_5005× 10^14 M_ . In this paper, we present a LOw Frequency ARray (LOFAR) 144 MHz detection of a radio halo in the galaxy cluster Abell 990 with a mass of M_500=(4.9± 0.3)× 10^14 M_ . The halo has a projected size of 700 kpc and a flux density of 20.2± 2.2 mJy or a radio power of 1.2± 0.1× 10^24 W Hz^-1 at the cluster redshift ( z = 0.144) that makes it one of the two haloes with the lowest radio power detected to date. Our analysis of the emission from the cluster with Chandra archival data using dynamical indicators shows that the cluster is not undergoing a major merger but is a slightly disturbed system with a mean temperature of 5 keV . The low X-ray luminosity of L_ X=(3.66± 0.08)× 10^44 erg s^-1 in the 0.1–2.4 keV band implies that the cluster is one of the least luminous systems known to host a radio halo. Our detection of the radio halo in Abell 990 opens the possibility of detecting many more haloes in poorly explored less massive clusters with low-frequency telescopes such as LOFAR, Murchison Widefield Array (MWA, Phase II), and upgraded Giant Metrewave Radio Telescope (uGMRT).